CD4+ lymphocytopenia due to common variable immunodeficiency mimicking AIDS. Issue 4 (April 1994) - Kaczmarski, R S; Webster, A D; Moxham, J; Davison, F; Sutherland, S; Mufti, G J
Abstract : There are an increasing number of published reports of patients with acquired immunodeficiency without evidence of HIV infection, who have been labelled as having "idiopathic CD4+ lymphocytopenia". The case is reported here of a young man who presented with Pneumocystis carinii pneumonia (PCP), CD4+ lymphopenia, and hypogammaglobulinaemia attributable to common variable immunodeficiency (CVID). The presentation of this condition, with many of the clinical and laboratory features of AIDS, highlights CVID as a diagnosis to be considered in the differential diagnosis of CD4+ lymphocytopenia.